(untitled) (Research, Society and Development, 2022)
Objective: to map the original articles on nursing and patient safety in the surgical center available in Brazilian databases. Method: Descriptive and bibliometric study, with a quantitative approach, carried out in the LILACS and BDENF databases from 2019 to 2022. Results and Discussion: 15 articles were selected, descriptively analyzed regarding the title of the articles, year of publication, training of authors, object, methodology used and the region where the studies took place. A total of 15 articles were identified that met the inclusion criteria. The years with the highest number of publications were 2019 (40%) and 2020 (33.3%) and the authors of the articles were trained as nurses (99%), only one doctor (1%). The region with the greatest representation of studies was the Southeast (66.7%), followed by the South (26.6%), respectively. The methodological approach most adopted by the researchers was qualitative (60.2%) and the main theme dealt with the surgical safety checklist/checklist (59.9%). Conclusion: Scientific production in this area has been concentrated in the Southeast/South axis and having as its object the surgical safety checklist. However, what has been published is focused on the perioperative period, demonstrating a correlation between studies and nursing practice in the safety of surgical patients.